TFClass: expanding the classification of human transcription factors to their mammalian orthologs. Issue Volume 46:Issue D1(2018) (26th October 2017) - Wingender, Edgar; Schoeps, Torsten; Haubrock, Martin; Krull, Mathias; Dönitz, Jürgen
Abstract: TFClass is a resource that classifies eukaryotic transcription factors (TFs) according to their DNA-binding domains (DBDs), available online at http://tfclass.bioinf.med.uni-goettingen.de . The classification scheme of TFClass was originally derived for human TFs and is expanded here to the whole taxonomic class of mammalia. Combining information from different resources, checking manually the retrieved mammalian TFs sequences and applying extensive phylogenetic analyses, >39 000 TFs from up to 41 mammalian species were assigned to the Superclasses, Classes, Families and Subfamilies of TFClass. As a result, TFClass now provides the corresponding sequence collection in FASTA format, sequence logos and phylogenetic trees at different classification levels, predicted TF binding sites for human, mouse, dog and cow genomes as well as links to several external databases. In particular, all those TFs that are also documented in the TRANSFAC ® database (FACTOR table) have been linked and can be freely accessed. TRANSFAC ® FACTOR can also be queried through an own search interface.